Attenuation of Microbiotal Dysbiosis and Hypertension in a CRISPR/Cas9 Gene Ablation Rat Model of GPER1. Issue 5 (November 2018) - Waghulde, Harshal; Cheng, Xi; Galla, Sarah; Mell, Blair; Cai, Jingwei; Pruett-Miller, Shondra M.; Vazquez, Guillermo; Patterson, Andrew; Vijay Kumar, Matam; Joe, Bina
Abstract : G-protein–coupled estrogen receptor, Gper1, has been implicated in cardiovascular disease, but its mechanistic role in blood pressure control is poorly understood. Here, we demonstrate that genetically salt-sensitive hypertensive rats with complete genomic excision of Gper1 by a multiplexed guide RNA CRISPR (Clustered Regularly Interspaced Short Palindromic Repeats)/Cas9 (CRISPR associated proteins) approach present with lower blood pressure, which was accompanied by altered microbiota, different levels of circulating short chain fatty acids, and improved vascular relaxation. Microbiotal transplantation from hypertensive Gper1 +/+ rats reversed the cardiovascular protective effect exerted by the genomic deletion of Gper1 . Thus, this study reveals a role for Gper1 in promoting microbiotal alterations that contribute to cardiovascular pathology. However, the exact mechanism by which Gper1 regulates blood pressure is still unknown. Our results indicate that the function of Gper1 is contextually dependent on the microbiome, whereby, contemplation of using Gper1 as a target for therapy of cardiovascular disease requires caution. Abstract : Supplemental Digital Content is available in the text.